ECONOMIC EMPOWERMENT THROUGH INCOME GENERATING of e-WARONG KUBE - Komang Monday Sari; Yuce Sariningsih (Universitas Pasundan, 2018)
This research entitled Economic Empowerment through Income Generating of e-Warong KUBE with the aims and purpose of this research were to describe and analyse 1) Economic empowerment of e-warong KUBE, 2) Various factors that influence business implementation, 3) Identify several effort due to overcome barrier on e-Warong KUBE’s implementation.and practical implication of social work intervention on e-warong KUBE development. The research method employed a qualitative approached which relied largely on interpretative and critical approaches to social work science. The data gathering used a documenting real events, recording what informant said (with words, gestures, and tone), observing specific behaviors, studying written documents, and participant observation. In this research, the number of informant were 6 (six) actors related to e-warong KUBE. Research finding showed that the economic empowerment through KUBE still in lower level caused by barrier both in form of internal and external factor, lack of entrepreneurial spirit of actor who managed e-warong KUBE, group dynamic still weak and unfamiliar to digital transaction. The recommendation were to conduct socialization of digital transaction in form of business training with involved social advisor, business advisor, Board of Social Affairs West Java Province as well as Bank Negara Indonesia (BNI) and Indonesian of Logistic Board (Bulog).